Photoluminescence, Impedance, Thermal Characteristics and Hirshfeld Surface Analysis of Potassium Bisulphate Single Crystals for Third Order NLO Applications - Thilaga, K.; Selvarajan, P.; Kader, S.M. Abdul (East European Journal of Physics, 2021)
Good quality potassium bisulphate (KHS) single crystals have been grown by slow evaporation method at room temperature. The KHS crystal was found to be crystallizing in orthorhombic crystal structure with Pbca space group. The photoluminescence behaviour of the crystal was analysed in the visible region. This study disclosed that the grown KHS crystal has intense blue emission peak at 490 nm. Impedance analysis was performed to investigate the frequency dependent electrical characteristics at various temperatures. From the impedance studies the bulk resistance, grain boundary resistance and DC conductivity values of the grown crystal were found out. The KHS crystal was subjected to TGA/DTA and the results have been investigated. The electrical parameters like Fermi energy and average energy gap of KHS crystal have been determined. The evaluated values are used to estimate the electronic polarizability. The intermolecular interactions were predicted using Hirshfeld surface analysis. This analysis exhibited that the utmost contribution to the crystal structure was the K⋯O (46.7%) interaction. The 2D fingerprint plot provides the percentage contribution of each atom-to-atom interaction. Since KHS material is a centrosymmetric crystal, it could be used for third order nonlinear optical (NLO) applications.